The development of the unified Baltic Sea Chart Datum 2000 (BSCD2000) height transformation grid: an unprecedented example of height system unification based on state-of-the-art marine geoid modelling - Joachim Schwabe; Sander Varbla; Jonas Ågren; Hergeir Teitsson; Artu Ellmann; Gunter Liebsch; René Forsberg; Gabriel Strykowski; Mirjam Bilker-Koivula; Ivars Liepiņš; Eimuntas Paršeliūnas; Kristian Keller; et al. (Journal of Geodesy, 2026)
The shallow Baltic Sea is a vital waterway with dense shipping traffic, requiring accurate and reliable nautical charts for safe navigation. Until recently, different realisations of the mean sea level were used in the paper charts of each country, sometimes even between harbours. This created obstacles for the digitalisation of ship navigation, including electronic nautical charts combined with satellite-based positioning. To resolve this, the Baltic Sea Hydrographic Commission decided in 2013 to introduce the Baltic Sea Chart Datum 2000 (BSCD2000) as a common height/depth reference system for the maritime sector in the Baltic Sea. The new reference level for all depth and water level information is strictly the quasigeoid, which is practically identical to the geoid at sea. The BSCD2000 is defined in accordance with the European reference systems: the European Terrestrial Reference System 1989 (ETRS89) for ellipsoidal coordinates and the European Vertical Reference System (EVRS) for physical heights. This enables the practical implementation of the zero level through a seamless height transformation grid with standard uncertainties of approximately 1–2 cm, which is harmonised with national coordinates, heights, and height reference surfaces. To the authors’ knowledge, this level of harmonisation is unprecedented in the maritime sector and exemplifies the value of the unification of height systems in geodesy. The paper outlines the foundations of the BSCD2000 and the approach to construct the BSCD2000 height transformation grid. While the computation of the gravimetric marine quasigeoid model is based on well-established methods, special focus is placed on practical harmonisation across national borders and along the coastline. To this end, a novel fitting and blending scheme based on distance maps was developed. Finally, comparison of the new gravimetric marine quasigeoid solution with a preliminary geometric marine geoid model based on SWOT altimetry data and hydrodynamic modelling confirmed good agreement within a few centimetres in most areas of the Baltic Sea.

Advantages of low-cost LiDAR sensors in surveying underground utility networks - Angelina Jerjomina; Sander Varbla (Tunnelling and Underground Space Technology, 2025)

Iterative data assimilation approach for the refinement of marine geoid models using sea surface height and dynamic topography datasets - Sander Varbla; Artu Ellmann (Journal of Geodesy, 2023)

The Influence of Bathymetry on Regional Marine Geoid Modeling in Northern Europe - Sander Varbla (Journal of Marine Science and Engineering, 2022)
Although Northern Europe has been the target area in many regionwide geoid determination studies, the research has been land-focused, neglecting bathymetry information. With new projects, such as the Baltic Sea Chart Datum 2000, the attention is shifting toward the marine geoid. Hence, consideration for bathymetry has become relevant, the influence of which is studied. In the relatively shallow Baltic Sea, accounting for bathymetry-based residual terrain model reduction during gravity data processing induces marine geoid modeling differences (relative to neglecting bathymetry) mainly within 2 cm. However, the models can deviate up to 3–4 cm in some regions. Rugged Norwegian coastal areas, on the other hand, had modeling improvements around a decimeter. Considering bathymetry may thus help improve geoid modeling outcomes in future Northern Europe geoid determination projects. Besides using the conventional precise GNSS-leveling control points, the paper also demonstrates the usefulness of shipborne GNSS and airborne laser scanning-derived geoidal heights in validating geoid modeling results. A total of 70 gravimetric geoid solutions are presented, for instance, by varying the used reference global geopotential models. According to the comparisons, GOCO05c-based solutions generally perform the best, where modeling agreement with GNSS-leveling control points reached 2.9 cm (standard deviation) from a one-dimensional fit.

Validation of Marine Geoid Models by Utilizing Hydrodynamic Model and Shipborne GNSS Profiles - Sander Varbla; Artu Ellmann; Nicole Delpeche-Ellmann (Marine Geodesy, 2020)